2019
DOI: 10.1016/s2215-0366(18)30302-x
|View full text |Cite|
|
Sign up to set email alerts
|

Factors affecting implementation of digital health interventions for people with psychosis or bipolar disorder, and their family and friends: a systematic review

Abstract: Digital health interventions present an important opportunity to improve healthcare for people affected by psychosis or bipolar disorder, but despite their potential there have been widespread difficulties in integrating and implementing them into clinical settings. This review aims to identify factors affecting implementation of digital health interventions for people affected by psychosis or bipolar disorder. We searched 7 databases and synthesised data from 26 studies using the Consolidated Framework for Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
117
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 59 publications
8
117
0
3
Order By: Relevance
“…Taking the example of a remote patient monitoring system, the study con rmed critical barriers to the implementation of new digital health technologies [8,10,46] and showed that these also apply to the intensive care setting. The proposed implementation framework for digital health technology in the ICU includes practical strategies to overcome these barriers while using previously identi ed facilitators that can be applied before, during, and in the general context of an implementation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Taking the example of a remote patient monitoring system, the study con rmed critical barriers to the implementation of new digital health technologies [8,10,46] and showed that these also apply to the intensive care setting. The proposed implementation framework for digital health technology in the ICU includes practical strategies to overcome these barriers while using previously identi ed facilitators that can be applied before, during, and in the general context of an implementation.…”
Section: Discussionmentioning
confidence: 94%
“…Transferable discoveries from these strategies and the strategies we propose to be applied before implementation (Promote adaptability, Conduct local needs assessment, Assess for readiness, and identify barriers and facilitators) could be used to improve the adaptability and needs-orientation of the intervention. Adaptability and user-centered design have been identi ed as key facilitators of digital health implementation in other settings [8,46,47]. To create the respective conditions, developers and providers of digital health technologies should actively participate in the implementation processes by taking advantage of the valuable feedback from clinical stakeholders and adapting their products in the spirit of user-centered design [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that resources regarding time, staff, funding and space for the implementation of a novel intervention in the explored services are perceived as limited. Lack of nancial and human resources have been found to be key implementation roadblocks for digital interventions for people with psychosis [24]. The cost of tablets overall was not considered to be a major burden in the implementation of DIALOG+ in the context of SEE.…”
Section: Discussionmentioning
confidence: 99%
“…Excluding participants for reasons not contained in the protocol likely has implications for the replicability and robustness of research ndings because the selection criteria are obscured (61) and samples likely become biased. Therefore, there is need to learn more about why this apparent " ltering" happens (from the perspective of mental health staff)-particularly in digital interventions for psychosis where little is currently known (13) and there may be assumptions about ability of people with psychosis to use technology (12).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond widespread societal concern about the negative impacts of digital technology within daily life (11), there may be recruitment challenges in mental health care research such as concerns patients may struggle to use a digital device (12). However, systematic review evidence suggests that these effects are not yet understood because trial recruitment is not covered in depth in studies of implementation barriers for digital interventions for psychosis (13).…”
Section: Introductionmentioning
confidence: 99%